Outdoor alcohol advertising in Johannesburg residential areas - Kalideen, Savera (My University, 2018)
Introduction Alcohol use is associated with many health-related and social problems, such as injuries and violence, as well as increased risk of HIV infection. Alcohol consumption among South African youth aged 15 to 24 years is high. One driver of increased consumption among young people is alcohol advertising. The WHO Global Strategy on Alcohol (2010) recommends evidence-based best-practice interventions to reduce alcohol-related harm. The Global Strategy calls for a regulation in the content and volume of marketing and restricting or banning promotions in connection with activities such as festivals or competitions that target young people, and the regulation of media-based direct and indirect marketing. There is very little published information on the extent and characteristics of outdoor alcohol advertising in South Africa. This study aimed to describe the number, location, characteristics and content of outdoor alcohol advertising and branding found in central Johannesburg and to compare the characteristics and content of adverts in lower and higher socioeconomic status areas. Methodology A cross-sectional study was conducted to identify and analyse all outdoor alcohol advertisements in a five-kilometre radius in central Johannesburg in 2014. Photographs of each alcohol advertisement were taken and the Global Positioning System (GPS) location, type and other characteristics were recorded on a coding sheet. The content of the advertisements based on the photographs was captured using a content coding sheet and linked to the GPS coordinates. Using income information from the City of Johannesburg in 2013, lower and higher economic status areas were defined. Descriptive analysis of the content and characteristics of the outdoor advertisements was conducted. The characteristics and content of advertisements in the higher and lower socioeconomic status areas were compared. Results There were 346 alcohol advertisements identified in this study. The most commonly advertised alcohol was for beer (71.1%) followed by cider (12%) and whiskey (5.6%). About 4.1 % of the adverts were for liqueurs and 2% were for cognac. Vodka and champagne made up less than 2% each of the adverts. Most of the alcohol advertisements and branding (66.8%) were found in the lower socioeconomic status areas of Hillbrow and Berea with just over one-third of all alcohol advertisements (33%) found in all other areas of the study area in Johannesburg. Nearly half of the alcohol adverts were posters (41.0%) followed by adverts painted on blackboards (19.7%). Most alcohol advertisements were located outside bars, taverns and liquor vendors (75.4%). Full advertisements which showed the product and a message about the product as well as a picture of other things such as cars, people and scenery made up 65.3% of all advertisements. Advertising in lower socioeconomic status areas were characterised by displaying the price of the alcohol and were sometimes hand-painted rather than being professionally made. Conclusion The study found differences in the number, characteristics and content of outdoor alcohol advertisements in central Johannesburg, South Africa. There were more advertisements in the lower socioeconomic status areas than in the higher socioeconomic suburbs. There are no restrictions on outdoor alcohol advertising in South Africa, which has led to the proliferation of outdoor alcohol advertising There is a need for a policy on alcohol advertising, which also includes regulation and monitoring of all alcohol advertisements, including outdoor alcohol advertising . More research is also required to show the impact of alcohol advertising on consumption in South Africa as most of the available evidence on this association is from outside the country. A convention similar to the Framework Convention on Tobacco Control is required as there is currently no global mechanism to regulate and govern alcohol advertising and marketing.
A research report submitted to the School of Public Health, Faculty of Health Sciences, University of Witwatersrand in partial fulfilment of the requirements for the degree of Master of Public Health, 2018
Keywords: Advertising--Alcohol beverages